PEMBERDAYAAN KELOMPOK WANITA TANI (KWT) MELALUI PEMANFAATAN LALAT TENTARA HITAM DAN Trichoderma sp. SEBAGAI AGEN BIOFUNGISIDA DAN PEMBUATAN PUPUK ORGANIK DI MAKASSAR, SULAWESI SELATAN - Dermawan, Rahmansyah; Permana, Agus Dana; Faizal, Ahmad (Jurnal Dinamika Pengabdian, 2020)
Chili cultivation activities in various regions encounter many problems. Therefore, this encouraged us to develop technology transfer on utilization of black soldier fly (Hermetia illucens), Trichoderma , and organic fertilizer through community service activities. This activity was a collaboration between Institut Teknologi Bandung and Hasanuddin University to transfer knowledge and skills to farmer women group members on utilization of black soldier fly and beneficial microorganisms such as Trichoderma . Both agents could be employed in converting organic waste into organic fertilizer for chilli plantation plants in Makassar, South Sulawesi. The methodology used in this activity including explanation of the important role of both black soldier flies and Trichoderma  sp. in the chili cultivation system, compost making practices, as well as training and assistance during chili cultivation. Outputs in this activity were increased knowledge and skills of farmer women groups regarding the utilization of black soldier flies and Trichoderma , the ability to make compost, and increased skills of farmer women group members in chili cultivation. It can be concluded that the introduction of black soldier flies and Trichoderma  was responded very well by farmer women group members as well as fully supported by village officials and stakeholders at the activity site. Not only did farmer group members get new information and insights, but they also gained skills in the use of black soldier flies and Trichoderma  as biodecomposers and biofungicide agents. This activity was expected to increase the motivation of farmer women groups in improving the quality of life and independence in the family by optimizing their backyard for the cultivation of horticultural crops such as chili. The harvested chili was successful and subsequently delivered to consumers. The results of this activity were also disseminated at the National Seminar on Community Services, carried out by the Jurnal Dinamika Pengabdian, UNHAS in August 2019.Keywords: Farmer women group, black soldier fly, Trichoderma, organic fertilizer. ABSTRAKKendala yang dihadapi pada kegiatan budidaya cabai di berbagai daerah mendorong alih teknologi pemanfaatan lalat tentara hitam atau Black Soldier Fly (Hermetia illucens), Trichoderma  serta pupuk organik melalui kegiatan pengabdian kepada masyarakat. Kegiatan ini merupakan kolaborasi dari Institut Teknologi Bandung dan Universitas Hasanuddin yang bertujuan untuk memberikan pengetahuan dan keterampilan kepada anggota kelompok wanita tani (KWT) dalam memanfaatkan lalat tentara hitam dan mikroorganisme bermanfaat seperti Trichoderma. Kedua agen hayati ini dapat dimanfaatkan untuk mengkonversi limbah organik menjadi pupuk yang bermanfaat untuk budidaya tanaman cabai di Makassar, Sulawesi Selatan. Metode yang digunakan berupa penjelasan tentang peran lalat tentara hitam dan mikroorganisme Trichoderma  spp. dalam sistem budidaya tanaman cabai, praktik pembuatan kompos, serta pelatihan dan pendampingan dalam budidaya cabai. Luaran pada kegiatan ini adalah meningkatnya pengetahuan dan keterampilan anggota KWT mengenai pemanfaatan lalat tentara hitam dan Trichoderma, kemampuan dalam membuat kompos, serta meningkatnya keterampilan anggota KWT dalam budidaya cabai. Dari kegiatan yang dilaksanakan dapat disimpulkan bahwa konsep pengenalan lalat tentara hitam dan Trichoderma  kepada anggota KWT mendapat respons yang sangat baik serta didukung penuh oleh aparat desa dan berbagai pemangku kepentingan di lokasi penyuluhan. Anggota kelompok tani tidak hanya mendapat informasi dan wawasan baru, tetapi juga mereka mendapatkan keterampilan dalam pemanfaatan lalat tentara hitam dan Trichoderma  sebagai biodekomposer dan agen biofungisida. Budidaya cabai yang yang dilaksanakan oleh anggota KWT berproduksi dengan baik dan hasilnya dapat dijual kepada konsumen. Hasil kegiatan ini juga diseminarkan dalam Seminar Nasional Pengabdian Masyarakat yang dilaksanakan oleh Jurnal Dinamika Pengabdian Pengabdian, UNHAS pada Agustus 2019.Kata kunci: Kelompok Wanita Tani, lalat tentara hitam, Trichoderma, pupuk organik.